The intercorporeal unconscious: a reply to discussions by Wolff-Bernstein and Kabasakalian-McKay - Iwer-Docter, Lukas; Kristensen, Stefan (Psychoanalytic dialogues, 2024)
We are deeply grateful for the benevolent, precise inspiring replies to our article. In our reply we present the research context of our article rooted in a phenomenological analysis of French psychoanalytic approaches to an intercorporeal understanding of the unconscious. We discuss different aspects of the comments by Wolff-Bernstein and Kabasakalian-McKay, namely the role of Hegelian and Lacanian aspects in Doltos psychoanalytic approach, Doltos understanding of the origin and development of the self in intersubjective relations, the dialectics between the individual and the collective in Doltos thinking and the necessary distinction between verbal and nonverbal aspects of communication.